Women’s Woodland Owner Network: A Comparative Case Study of Oregon (the United States) and Austria - Pipiet Larasatie; Dagmar Karisch-Gierer; Alice Ludvig (Land, 2022)
Gender equality, as a preferred social norm based on both ethical considerations and legislative demands, can be boosted by networking. However, the concept of organizational networks is too often associated with old boys’ clubs or old boy networks that effectively exclude women, thus limiting their potential. As a result, there is a movement to form women-inspired networks, to address the experiences of women with a goal for increasing their perceptions of belonging and engagement. So how do such networks operate in practice? This research focuses on the organizational differences and commonalities in two women’s woodland owner networks, one in the US and one in Austria, in order to understanding how participation in networks influence the advancement of women in the forest sector. Based on expert interviews, we found that both cases well reflect current networking potential for strengthening the capabilities of women engaging in network activities. Regardless of country women in similar circumstances tend to have similar networks. Yet, there are some differences even among these organized networks operating with similar targets. Results also show the limitations of sole networking approaches for the enhancement of women’s positions in the men-dominated forest sector. We suggested more action in terms of active equality policies, such as mentoring/networking programs, family friendly policies, and quota/sensibilization measures for boards and selection committees to increase the gender balance in the sector and its related industries.